Validity and reliability of short forms of parental-caregiver perception and family impact scale in a Telugu speaking population of India. Issue 1 (December 2016) - Kumar, Santhosh; Kroon, Jeroen; Lalloo, Ratilal; Johnson, Newell
Abstract Background Parental-Caregiver Perception Questionnaire (P-CPQ) and Family Impact Scale (FIS) are commonly used measures to evaluate the parent's perception of the impact of children's oral health on quality of life and family respectively. Recently, shorter forms of P-CPQ and FIS have been developed. No study has sought to validate these short forms in other languages and cultures. This study aimed to evaluate the validity and reliability of FIS, 8 and 16-item P-CPQ in a Telugu speaking population of India. Methods For this cross-sectional study, a multi-stage random sampling technique was used to recruit 11–13 year-old schoolchildren of Medak district, Telangana, India and their parents (n = 1342). Parents were approached with questionnaires through their children who underwent clinical examinations for dental caries, fluorosis and malocclusion. The translated versions underwent pilot testing (n = 40), test-retest reliability was also assessed (n = 161). Results The overall summary scale and subscales of the short forms of P-CPQ and FIS failed to discriminate between the categories of dental caries severity. Also, malocclusion status was not related to the domain or overall scores of both the short forms of P-CPQ. There were significant differences in subscale and overall scores of 16 and 8-item P-CPQ and FIS between the fluorosis categories. Both 16 and 8-item P-CPQ summary scales were significantly related to parent's global rating of oral health (16-item, r = 0.30, p < 0.01; 8-item, r = 0.28, p < 0.01) and overall wellbeing (16-item, r = 0.22, p < 0.01; 8-item, r = 0.22, p < 0.01), thereby exhibiting good construct validity. However, the correlation of emotional and social wellbeing scales of short forms of P-CPQ and FIS with global ratings was of low strength. Cronbach's alphas for FIS, 16-items and 8-items P-CPQ scales were 0.78, 0.83 and 0.71 respectively, while the Intra-Class Correlation coefficients were 0.752, 0.812 and 0.816 respectively. Cronbach's alphas for most of the subscales of short forms of P-CPQ were less than 0.7. Conclusions The overall scales of 16 and 8-items P-CPQ scales demonstrated good construct validity while the construct validity of FIS was questionable. Discriminant validity of all the three instruments was good only in relation to fluorosis. Overall scales of all three short forms exhibited acceptable internal consistency and reliability on repeated administrations.